Table 1_Immune checkpoint inhibitor therapy in advanced cancer: clinical association of irAEs type, inflammatory markers and efficacy.docx - Mengying Qian (2541466) (2025)
Background Immune checkpoint inhibitors (ICIs) improve survival in advanced cancers but are associated with immune-related adverse events (irAEs), whose prognostic impact remains debated. The role of systemic inflammatory biomarkers is also not fully defined. Methods This research merged a comprehensive systematic review and meta-analysis of 38 studies involving 55,966 participants with a multicenter retrospective cohort study of 870 patients receiving ICI therapy. The aim of this study was to examine the association between irAE characteristics and severity, and baseline inflammatory indicators (NLR, dNLR and PLR), with clinical outcomes, particularly survival (OS) and disease progression survival (PFS). The data were analyzed through time-dependent cox model and meta-analysis. Results Among 870 immunotherapy patients, 32.4% developed irAEs, predominantly grade 1-2 (83.9%). Severe irAEs (grade >2) significantly increased mortality (OS HR = 1.93). Organ-specific analysis identified endocrine (HR = 0.938, p < 0.001) and skin toxicity (HR = 0.763, p<0.001) as independent protective factors for OS, while hepatic (HR = 1.602, p=0.031) and cardiac toxicity (HR = 1.181, p=0.017) were risk factors. Elevated baseline inflammatory markers—MLR >0.47 (HR = 3.37), NLR >3.45 (HR = 2.24), and PLR >186.98 (HR = 2.10)—also predicted poorer OS. A meta-analysis confirmed that low-grade irAEs (grade ≤2) conferred significant survival benefit (OS HR = 0.54), particularly skin and endocrine toxicities. These findings support irAEs as biomarkers of immunotherapy response, with prognostic relevance shaped by severity and organ involvement. Conclusions The prognosis of irAEs depends on organ involvement and severity. Endocrine and skin toxicities confer survival benefits, while severe, hepatic, and cardiac events pose significant risks. Inflammatory markers predict survival but not irAE onset.